P114 Which antibody is more important for radiographic erosions in RA?. (20th April 2020) - Minocha, Amal; Kukran, Sebi; Yee, Philip; Nisar, Muhammad K
Abstract: Background: The presence of bony erosions in patients with RA is a marker of disease severity and once present they are largely irreversible. Previous studies have shown that those who are RF positive have more erosions than RF negative group. Likewise, ACPA is associated with increased bone loss and rapid erosive changes. The aim of our study was to determine which of these two antibodies is more strongly associated with erosive disease and whether being double +ve confers higher risk than single positive antibody status. Methods: A retrospective study of 774 patients diagnosed with RA at large university teaching hospital during the period of January 1981 and December 2018. Clinical records were reviewed to determine antibody status, date of diagnosis, duration of symptoms, DAS-28, age, ethnicity and whether the 1987 Rheumatoid Arthritis criteria was met. The presence of radiographic erosions at diagnosis were determined from reports of plain film radiographs of hands and feet of all patients. Chi square model was utilised to ascertain if there was a significant relationship among the four groups. Mann Whitney two-tailed U test was employed to determine the significance of relationship between the double negative group and other arms for all variables including disease duration and delta change in DAS28. Significance level was predefined at 0.05. Results: All patients fulfilled the 2010 ACR/EULAR criteria. 240 (31%) patients were male and 534 (69%) were female with an age range of 17 to 90 years for the cohort. The duration of symptoms ranged for the patient cohort from 0.5 to 250 months with a median of 6 months while the duration of disease ranged from 4 to 455 months with a median of 49 months. DAS 28 ranged from 1.19 to 8.4 with a median of 4.4. 367 (47%) were positive for both RF and ACPAs, 87 (11%) were positive for RF alone, 66 (9%) were positive for ACPA alone and 254 (33%) were antibody negative. There were a total of 127 patients with erosions at the time of diagnosis. Patients in the double positive group had a significantly higher (p = 0.003) erosion burden compared to the double negative group i.e. 21.5% in RF+/ACPA+ versus 11.0% in RF-/ACPA- group. The erosion burdens in RF+/ACPA- and RF-/ACPA+ groups were 13.7% and 12.1% respectively. Conclusion: This is the first real world study to demonstrate the radiographic erosive burden in the RA cohort with respect to RF/ACPA status. Our results show that patients RF+/ACPA+ have nearly two-fold higher incidence of radiographic erosions than patients who are RF-/ACPA-. Patients with single antibody positivity have a trend towards higher erosive burden compared to the double antibody negative group however it's the combination of two antibodies which is strongly associated with erosive disease. Disclosures: A. Minocha None. S. Kukran None. P. Yee None. M.K. Nisar None.